Health literacy in people living with mental illness: A latent profile analysis. (October 2019) - Degan, Tayla J.; Kelly, Peter J.; Robinson, Laura D.; Deane, Frank P.; Wolstencroft, Keren; Turut, Serhat; Meldrum, Rebecca
Highlights: Participants struggled most when appraising health information, navigating the healthcare system, and finding good health information. Three health literacy profiles were identified; low health literacy, moderate health literacy, and high health literacy. When compared to other populations the current sample's health literacy experiences were most consistent with a substance use disorder population. When compared to the general population, those living with a mental illness had lower health literacy scores. Abstract: Health literacy comprises cognitive and social skills that enable people to understand health information and maintain good health. Research examining the health literacy of people living with mental illness is scarce. The aim of the present study was to identify distinct subgroups of health literacy in individuals attending mental health treatment and determine if profiles and health literacy levels differ from other populations accessing healthcare services and on health characteristics. Participants ( N = 325) were attending Neami National Australia services. Participants completed the multidimensional Health Literacy Questionnaire. Latent profile analysis was conducted to identify health literacy profiles. Participants reported lowest health literacy scores in appraising health information, navigating the healthcare system, and finding good health information. Three health literacy profiles were identified; low (20.4%), moderate (61.3%), and high (18.3%). Compared to the other populations (i.e. private hospital patients, men with prostate cancer, older individuals with diabetes, general population, people attending substance dependence treatment), the current sample tended to have lower health literacy scores. The findings highlight the need to increase overall health literacy and consider an individualised approach to enhance specific health literacy domains.